2021
DOI: 10.1111/mcn.13171
|View full text |Cite
|
Sign up to set email alerts
|

Fussy eating in toddlers: A content analysis of parents' online support seeking

Abstract: The development of healthy eating habits in childhood is essential to reducing later risk of obesity. However, many parents manage fussy eating in toddlerhood with ineffective feeding practices that limit children's dietary variety and reinforce obesogenic eating behaviours. Understanding parents' feeding concerns and support needs may assist in the development of feeding interventions designed to support parents' uptake of responsive feeding practices. A total of 130 original posts by parents of toddlers (12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Thus, differential pressure to eat may be used in an attempt to ensure that lighter weight and more food avoidant siblings consume a sufficient amount and variety of food to facilitate growth and weight gain during early childhood. Despite this, evidence indicates that the use of pressure to eat may be ineffective or counter-productive in influencing child eating behaviours (Fraser, Markides, Barrett, & Laws, 2021).…”
Section: Synthesis Of Evidencementioning
confidence: 99%
“…Thus, differential pressure to eat may be used in an attempt to ensure that lighter weight and more food avoidant siblings consume a sufficient amount and variety of food to facilitate growth and weight gain during early childhood. Despite this, evidence indicates that the use of pressure to eat may be ineffective or counter-productive in influencing child eating behaviours (Fraser, Markides, Barrett, & Laws, 2021).…”
Section: Synthesis Of Evidencementioning
confidence: 99%
“…The language properties present in messages used to solicit informational support were associated with the volume of feedback they received from online community members. The results of this project also offer more focused insights about the potential implications of approach behaviors in support seeking (Goldsmith, 1995). Prior research has linked approach behaviors with higher quality emotional support from providers (Rains et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have documented the presence (Blight et al, 2015)-or relative absence (Mikal et al, 2021)-of informational support seeking messages on social network sites. Scholars studying posts made to the online community Reddit about fussy eating among toddlers reported that almost half of all the posts they examined involved requests for practical advice and tips (Fraser et al, 2021). Other work has focused on the types of messages that elicit informational support responses.…”
Section: Illness and Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of access to traditional means of support during the pandemic led many parents to seek parenting information and support online through social media networks, which was already becoming an increasingly common practice (Ammari et al, 2014 ; Mandell & Salzer, 2007 ), particularly during stressful periods (Haslam et al, 2017 ; Lupton, 2016 ) and among parents who live far from family and friends (Drentea & Moren‐Cross, 2005 ). Pre‐pandemic research found that parents look to social media networks to obtain social support that helps them cope with their specific stressors and matches their particular needs (Green‐Hamann & Sherblom, 2014 ), such as for parents of children who are fussy eaters (Fraser et al, 2021 ), children with undiagnosed medical needs (Deuitch et al, 2021 ), children with disabilities (Ammari & Schoenebeck, 2015a ), and parents of adolescents (Doty & Dworkin, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%